Governing Cross-Border Data Flows: International Trade Agreements and Their Limits - Yik-Chan Chin; Jingwu Zhao (Laws, 2022)
In modern international competition and cooperation, digital trade rules centered on the cross-border flow of data have become a competitive advantage for countries. Under the guidance of commercial freedom, the United States chooses to actively promote the free flow of data across borders. The European Union has placed the protection of personal data rights before the cross-border flow of data through the General Data Protection Regulation (GDPR), and developing countries generally reserve space for industry policy interpretation. As one of the world’s largest economies, facing the needs of domestic industrial development and the pressure of international systems, China’s cross-border data flows’ policy is to ensure data flows under the premise of security, protection of personal information, seek international coordination of rules, and the freedom of transmission. The key question, therefore, is how to facilitate interoperability or find a middle ground among the divergent approaches in order to avoid the fragmentation of the digital trade system. The article suggests that a thin and narrowly scoped WTO agreement on e-commerce rules on cross-border data flows with sufficient policy space to accommodate different needs, policy preferences and priorities, and local contexts via legitimate exception provisions would be a welcome movement.